Synthesis and Characterization of Carboxy Methyl Cellulose-Based Hydrogel Cross-linked with Citric Acid - Pitaloka, Alia Badra; Rukmana, Alda Sadilillah; Nur’afiani, Tia Yufika (World Chemical Engineering Journal, 2021)
Hydrogel is a three-dimensional hydrophilic polymer network which is capable of absorbing large amounts of water, urine, blood, and other biological fluids. The applications of hydrogel are present in various fields such as pharmaceuticals, agriculture, food, and medical fields. Hydrogel is used as a wound dressing, in a drug release system, in diapers, in and menstrual products. The purpose of this research is to produce carboxymethyl cellulose (NaCMC) hydrogels using citric acid as the crosslinking agent, and to determine the optimum conditions to produce hydrogels with a high absorption capacity of liquids using various concentrations of citric acid. The first step of this research is to mix NaCMC and citric acid by stirring it with an agitator at room temperature until the mixture becomes homogeneous. Then, the mixture is casted in a petri dish and dried for 24 hours at 30°C. Then, the crosslinking reaction was carried out at 80°C for a certain time. After that, the gels are put out of the petri dish and tested to determine their values of water absorption capacity (swelling) and gel fractions. Lastly, the hydrogels are characterized using FTIR and SEM. The results showed that the NaCMC hydrogel with anhydrous citric acid with 10%-wt is the best with 3779.16% swelling ratio and gel fraction of 60%.